2013
DOI: 10.1155/2013/639184
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Thermal Comfort and Light Intensity with Sleep Quality and Eye Tiredness in Shift Work Nurses

Abstract: Environmental conditions such as lighting and thermal comfort are influencing factors on sleep quality and visual tiredness. The purpose of this study was the determination of the relationship between thermal comfort and light intensity with the sleep quality and eye fatigue in shift nurses. Method. This cross-sectional research was conducted on 82 shift-work personnel of 18 nursing workstations in Isfahan Al-Zahra Hospital, Iran, in 2012. Heat stress monitoring (WBGT) and photometer (Hagner Model) were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
1
20
0
4
Order By: Relevance
“…This study may also be a preface for more investigations for the development of factors influencing the design of workplace. [ 29 30 31 32 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…This study may also be a preface for more investigations for the development of factors influencing the design of workplace. [ 29 30 31 32 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although it could be difficult to compare the results of this study with those of other studies due to different study methods, in previous studies, results similar to ours have been found. Azmoon et al found that thermal comfort in the workplace was related to high quality sleep in a cross-sectional study [ 38 ]. Workers who have been exposed to organic solvents for a long period of time have a high prevalence of sleep apnea compared with the general population, and this can induce fatigue, daytime sleepiness, and decreased concentration [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known to date about how shiftwork with VDT affects ocular and visual symptoms. Azmoon et al [22] detected a relationship between thermal comfort, light intensity, sleep quality, and eye fatigue in night shift nurses. No reference is made to the use of VDT in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The second [15] did not specify whether or not they were health personnel. Azmoon et al [22] concluded that defects in environmental conditions, such as thermal comfort and illumination intensity, increased eye fatigue in night shift nurses; however, the authors’ work was not aimed at the use of VDTs in the workplace and how it affects eye fatigue. Also, in 2019, a review [23] about CVS in radiologists concluded that long hours in front of computer monitors make the work of radiologists quite similar to that of computer professionals.…”
Section: Introductionmentioning
confidence: 99%